The application of oral hygiene using Betadine mouthwash to enhance self-care in patients with non-hemorrhagic stroke (NHS) in the ICU at Bhayangkara Hospital Makassar - Fardi Fardi; Dardin; Farhan Abdiyansa (Indonesian Journal of Nursing and Health Care, 2025)
Background: Stroke is a disorder of cerebral circulation that results in sudden neurological deficits due to ischemia or hemorrhage. According to SIKI, interventions for Self-Care Deficit nursing problems include oral hygiene treatment using Betadine mouthwash, which is an independent nursing intervention.Objective: This study aimed to explore the impact of oral hygiene treatment using Betadine mouthwash in patients with Non-Hemorrhagic Stroke (NHS) and Self-Care Deficit nursing problems in the nursing unit at Bhayangkara Hospital Makassar.Methods: A qualitative descriptive case study design was used, involving a single patient with NHS and Self-Care Deficit nursing problems. Oral hygiene treatment with Betadine mouthwash was administered over a period of 3 days to provide comfort and promote healing.Results: Evaluation results showed improvements after 3 days of oral hygiene care using Betadine mouthwash. The patient had no bad breath (1), felt comfortable in the teeth and mouth (5), had visibly cleaner teeth and mouth (5), saw improvement in lip mucosa (5), and consistently maintained oral hygiene (5).Conclusion: Oral hygiene treatment with Betadine mouthwash effectively improved oral health and self-care in patients with Non-Hemorrhagic Stroke (NHS) and Self-Care Deficit nursing problems.